Hardware and Software of Automated Control System of Plants' Water Well-Being - Matus, Svitlana; Matviychuk, Myroslav; Sych, Vladyslav; Matus, Olena (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The hardware of the automated control system of plants' water well-being and the software for all components of the system have been developed.